Government registering varieties of vegetables plants - basis of formation nationality varietal resurce - Н. В. Лещук; М. М. Зрібняк (Plant Varieties Studying and Protection)
In the article revealed the scientist basis of vegetables plants nationality varieties resource via government registering of new varieties and their right protection.